Biopolitics and Architecture of the Chilean Workers’ Insurance. Central Factory of Milk's residential complex - Campos Gajardo, Alicia (2023)
The biopolitical approach here presented, aims to interpret the morphological and programmatic characteristics of the residential complex of the Central Factory of Milk, considering the conceptualizations provided by M. Foucault on the notion of population and environment with the treatment of its vital processes for an economic availability of its productive forces. Located in the first industrial periphery of the city of Santiago, the Central Factory of Milk’s complex, is a residential group adjacent to the homonymous dairy factory. The complex also had community facilities, commerce, and a health clinic, which in its arrangement are seen as a unit, arranging daily life and its safeguards in terms of production. This residential and industrial complex has its origins in the management of the Workers’ Insurance Fund, the first Chilean and Latin American initiative for provision of health, sickness, and elderly workers' welfare, through contributions from employers, the State, and the hired workers. This institution articulated early on the healthiness of its members from the perspective of social medicine, taking care of the sanitary equipment for health care and welfare, but also planning the residential space and work conditions to strengthen their productive forces. This care for the workforce is understood here from a biopolitical perspective, recognizing the regulation and assurance strategies that, through a qualitative and relational methodology on specific documents, will be associated with architectural and urban aspects of residential, health, and productive programs of the residential complex of Central Factory of Milk.